Effect of Methods of Polyethylene Glycol Addition on Gas Poduction Parameters of Acacia seyal, Acacia ehrenbergiana and Capparis deciduas (Journal of Veterinary Medicine and Animal Production, 2021)
The aim of this study was to estimate the nutritive value and the effect of methods of poly ethylene glycol (PEG) addition as single dose and spilt doses on in vitro gas production kinetic of Acacia seyal, A. ehrenbergiana and Capparis deciduas leaves. Crude protein (CP), Crude fiber (CF), Ether Extract(EE), Ash, Nitrogen Free Extract, (NFE), Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Acid Detergent Lignin (ADL), and Total Condensed Tannin (TCT) were determined, In vitro Organic Matter Digestibility (IOMD) and Metabolizable Energy (ME) were calculated and in vitro gas production was carried out. Data were subjected to analysis of variance using complete randomize design. Chemical content were significantly (P≤ 0.05) varied among the species. Crude protein content ranged from 7.66 to 15.88%. ADF and NDF contents varied within species and ranged from 43.96 to 51.65% and 54.30 to 59.32 %, respectively. TCT content ranged from 1.98 to 3.26%. The addition of PEG as one dose and as split doses increased gas production in all species of trees. The single application of PEG resulted in higher gas production than the spilt application. The insoluble fraction (b), potential gas production (a+b), IOMD and ME were significantly (P≤ 0.05) increased with PEG addition. The improvement of IOMD and ME with the inclusion of PEG demonstrated the negative effect of tannins on digestibility and the addition of PEG by both methods may improve the nutritive value of trees leaves.
Keywords: Polyethylene Glycol; Acacia seyal; Acacia ehrenbergiana